Public opinion on renewable energy technologies and climate change in Peninsular Malaysia - Kardooni, Roozbeh; Yusoff, Sumiani; Kari, Fatimah; Moeenizadeh, Leila (Elsevier, 2018)
The development of renewable energy policies is necessary to ensure secure and sustainable energy supplies at reasonable costs and to address issues related to global climate change. Since the year 2000 in Malaysia (time of the 8th Malaysian Plan), renewable energy has been included as a key fifth element in the country's fuel policy along with hydro, coal, gas, and oil, and a target of obtaining 5% of the total energy supply from renewable sources was set, although it has not yet been reached. This work explores public opinions regarding climate change and renewable energy in Peninsular Malaysia. Probability sampling and a stratified technique were used to conduct a survey with subjects aged 20 years and over with higher education qualifications. The results showed that the majority of Malaysians are concerned about climate change and have heard about renewable energy. However, only two out of five people in Peninsular Malaysia have used renewable energy products. This finding can be explained by the high price of renewable energy products, lack of knowledge about government policies, and ineffective programs and initiatives.